The Role of Expectations on Exchange Rate Determination in Indonesia - Maryatmo, Rogatianus (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2023)
There are two purposes of this paper. Firstly, it deals with expectation formation. Secondly, it will be tested whether the expectation has a significant role in determining the current exchange rate in the case of Indonesian currency against the US dollar and Euro. This research will compare two kinds of expectation formation. Firstly, the expectation built from the fundamental economy is known as rational expectation formation. Secondly, the expectation formulated from past time series information, the Auto Regressive Moving Average (ARMA) model, is utilized. The steps to prove the role of expectation are stationary process, degree of integration, co-integration, and U-Theil's Inequality Coefficient Test (UTIC). It is found that both kinds of expectation formation have essential roles in determining the current exchange rate in Indonesia. However, according to UTIC criteria, a rational expectation better explains both current exchange rate movements.